How college experiences impact student learning outcomes: Insights from Chinese undergraduate students - Bai, Hua; Yu, Hongwei; Bantsimba N., Rogerland; Luo, Li (Frontiers in Psychology, 2022)
In recent years, student development and learning outcomes have become a central focus of quality higher education research. Identifying factors associated with student learning outcomes is the key to continuous quality improvement. The purpose of this study was to explore the impact of college experiences on student learning outcomes. A sample of 17,609 undergraduates from 23 Chinese colleges/universities were selected for the study and asked to complete the Chinese version of the College Student Experiences Questionnaire. Structural equation modeling analyses suggested academic and social activity involvement was an important factor influencing student learning outcomes. Campus facilities and the college environment also predicted student learning outcomes. Family background, on the other hand, exerted minimal influence on student learning outcomes. Students’ involvement in academic and social activities served as strong mediators between campus facilities/environment and student learning outcomes. The results highlighted the significance of providing high-quality college experiences. They also informed policymakers and practitioners of possible pathways to support student learning outcomes by enhancing students’ involvement in social and academic activities.